SISTEM PEMBAGIAN AIR UNTUK POLA TANAM PADI-PADI-JAGUNG DI PETAK TERSIER C6kn DAERAH IRIGASI MOLEK, DESA MANGUNREJO, KABUPATEN MALANG - Agus Suhardono, Winda Harsanti, Moch. Khamim (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2016)
Food is an important thing for humans and this number will be increased day by day because the number of humans increases. To fulfill this needs, good irrigation in farm is needed. Petak C6kn is an irrigation area in Kepanjen, District of Malang which is still operated. The purpose of this study is to determine whether the river water can provide irrigation needs with the pattern of crop is rice-rice-corn. From the analysis, the maximum needs of irrigation is 0,2161 m3/s. Availability of river water (dependable discharge) throughout the year ranges 0,163 m3/s to 0,245 m3/s. From the calculation and analysis, it can be concluded that the water river can fulfill irrigation needed all year. In another word, rotation way to give irrigation water is not needed. Keywords: irrigation, dependable discharge, rotation